Benzo‐Extended Cyclohepta[def]fluorene Derivatives with Very Low‐Lying Triplet States - Wu, Fupeng; Ma, Ji; Lombardi, Federico; Fu, Yubin; Liu, Fupin; Huang, Zhijie; Liu, Renxiang; Komber, Hartmut; Alexandropoulos, Dimitris I.; Dmitrieva, Evgenia; Lohr, Thorsten G.; Israel, Noel; et al. (Angewandte Chemie International Edition, 2022)
Open‐shell non‐alternant polycyclic hydrocarbons (PHs) are attracting increasing attention due to their promising applications in organic spintronics and quantum computing. Herein we report the synthesis of three cyclohepta[def]fluorene‐based diradicaloids (1–3), by fusion of benzo rings on its periphery for the thermodynamic stabilization, as evidenced by multiple characterization techniques. Remarkably, all of them display a very narrow optical energy gap (Egopt=0.52–0.69 eV) and persistent stability under ambient conditions (t1/2=11.7–33.3 h). More importantly, this new type of diradicaloids possess a low‐lying triplet state with an extremely small singlet–triplet energy gap, as low as 0.002 kcal mol−1, with a clear dependence on the molecular size. This family of compounds thus offers a new route to create non‐alternant open‐shell PHs with high‐spin ground states, and opens up novel possibilities and insights into understanding the structure–property relationships. Three open‐shell non‐alternant polycyclic hydrocarbons (PHs) based on the skeleton of cyclohepta[def]fluorene are synthesized via an efficient benzannulation stabilization strategy. The obtained persistent singlet diradicaloids have a narrow optical energy gap (0.52–0.69 eV). Moreover, variable‐temperature EPR measurements indicate that all of them have a low‐lying triplet state with an extremely small singlet–triplet energy gap.